(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article will talk about the use of textbooks in school education, its important factors. A reflection will be made on the useful and necessary aspects of the new textbook. There is talk about the influence of imagination on the mother tongue lessons and on the mother tongue, its beneficial factors.The introduction of the 7th grade to topics in the textbook of the native language.